2002
DOI: 10.5194/acp-2-55-2002
|View full text |Cite
|
Sign up to set email alerts
|

Field measurements of hygroscopic properties and state of mixing of nucleation mode particles

Abstract: Abstract. An Ultrafine Tandem Differential Mobility Analyser (UF-TDMA) has been used in several field campaigns over the last few years. The investigations were focused on the origin and properties of nucleation event aerosols, which are observed frequently in various environments. This paper gives a summary of the results of 10 nm and 20 nm particle hygroscopic properties from different measurement sites: an urban site, an urban background site and a forest site in Finland and a coastal site in western Irelan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 36 publications
(41 reference statements)
4
20
0
Order By: Relevance
“…7a and c). This diurnal trend corresponds well with those found by previous studies at the Hyytiälä site (e.g., Hämeri et al, 2001;Väkevä et al, 2002;Boy et al, 2004;Ehn et al, 2007). CFSTGC-derived κ values covary with AMS-derived inorganic volume fraction, daily temperature trends, and AMS f 44 data.…”
Section: Diurnal Variability Of κsupporting
confidence: 89%
“…7a and c). This diurnal trend corresponds well with those found by previous studies at the Hyytiälä site (e.g., Hämeri et al, 2001;Väkevä et al, 2002;Boy et al, 2004;Ehn et al, 2007). CFSTGC-derived κ values covary with AMS-derived inorganic volume fraction, daily temperature trends, and AMS f 44 data.…”
Section: Diurnal Variability Of κsupporting
confidence: 89%
“…Freshly emitted hydrophobic particles such as externally mixed black carbon particles are mostly in the fine modes. Besides, the significant Kelvin effect also leads to higher hygroscopic growth factors for particles in the coarse mode than for those in fine modes (Väkevä et al, 2002). For the coarse mode, the R 2 are between 0.3 and 0.6 under all the RH conditions.…”
Section: Impacts Of Pnsdmentioning
confidence: 90%
“…The ratio of the calculated to the measured CCN concentration for different mass fraction of ammonium sulfate (from 1.0 to 0.1) and five supersaturations is shown in Secondly, we assume that ammonium sulfate is externally mixed with insoluble material. Externally mixed aerosols were observed at many places (e.g., Väkevä et al, 2002) and have been assumed in many regional scale models (Koch et al, 1999;Chin et al, 2000;Boucher and Anderson, 1995;Barth et al, 2000). The insoluble aerosols are hydrophobic and do not act as CCN.…”
Section: Sensitivity To Aerosol Solubility and Mixing Statementioning
confidence: 99%
“…Two different types of mixture, internal mixture and external mixture, are often observed in field measurements (Väkevä et al, 2002;Schwarz et al, 2006) and used in model studies (Textor et al, 2006;Wang et al, 2010). For example, field measurements by Väkevä et al (2002) showed that externally mixed aerosol was sometimes observed at urban and forest sites in Finland and a coastal site in western Ireland. Schwarz et al (2006) presented results that the number fraction of internally mixed black carbon particles range from 0.2 to 0.8.…”
Section: F Yang Et Al: a Closure Study Of Cloud Condensation Nucleimentioning
confidence: 99%
See 1 more Smart Citation